HUBUNGAN KEPUASAN KERJA TERHADAP KOMITMEN STAF ORGANIK PERUSAHAAN MOBIL RENTAL - Widagdo, Nunnie (Teropong : Jurnal Manajemen dan Bisnis, 2020)
The aim of this research is to find the correlation between job satisfaction and organizational commitment on Car Rental organic staff (driver). Job satisfaction is related to number of major employee variables. such as turnover, absences, age, occupation and size of the organization in which an employee works. While organization commitment is degree which. is the employee identify and internalize the organizational values, which make the employee want to stay in organization. The researcher using the method ofdiscrepancy theory by Porter to figure out all ofthe aspects that capable ofincreasing or even decreasing the level ofjob satisfaction refer to the organizational commitment as the result ofthis research. The population ofsample is the organic staffin Car Rental Company, one ofthe biggest in Bandung, that has been used by many companies in Bandung. The researcher use the purposive sampling to gather all ofinfomation needed, wherejob satisfaction as variable X and organizational commitmen as variable Y. And this researchfind out that organizational commitment influence positively towardsjob satisfaction.